Спящая красавица: [сказка : детям до трех лет] / Шарль Перро ; [художник Л. Якшис] - Перро Шарль (Серия "Почитай мне сказку", 2017)
Экземпляры: ДБ (20201016) / Инвентарный номер: 52997 / Цена: 13.00 / Сис.шифр: Д / Авт.знак: П 27 / ГРНТИ: 17.82.93 / ББК: 84(4Фра)